2021
DOI: 10.1007/s12603-020-1532-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on the Relationship between Life-Space Mobility and Quality of Life in Older Adults during the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has led to abrupt restrictions of life-space mobility. The impact of shelter-in-place orders on older adults' health and well-being is still unclear. Objective: To investigate the relationship between life-space mobility and quality of life (QoL) in older adults with and without frailty during the COVID-19 pandemic. Design: Multicenter prospective cohort study based on structured telephone interviews. Setting: Four geriatric outpatient clinics in the metropolitan area of Sao P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 52 publications
(60 reference statements)
3
53
2
3
Order By: Relevance
“…Restrictions in life-space mobility (12,13) and in active aging scores (12) were observed in community-dwelling older people during the COVID-19 pandemic. Active aging was evaluated using a novel scale that encompasses older people's striving for well-being through activities pertaining to their goals, abilities, and opportunities (14).…”
Section: Introductionmentioning
confidence: 97%
“…Restrictions in life-space mobility (12,13) and in active aging scores (12) were observed in community-dwelling older people during the COVID-19 pandemic. Active aging was evaluated using a novel scale that encompasses older people's striving for well-being through activities pertaining to their goals, abilities, and opportunities (14).…”
Section: Introductionmentioning
confidence: 97%
“…Chen (2021) reported that older adults with pre-frailty or frailty expressed negative emotional reactions including anxiety and worry, toward COVID-19. Moreover, the presence of anxiety was independently associated with the impact of the COVID-19 pandemic on the quality of life of community-dwelling older adults (Saraiva, 2021). It is worth noting that frail women were particularly vulnerable to the effects on their quality of life during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 93%
“…Many factors are related to a decrease in their quality of life such as being housebound with no visitors, inevitable changes to diet, lack of physical exercise, reduced cognitive stimulation, withdrawal of functional support and rehabilitation therapies; that ultimately could lead to physical frailty and functional disability [2][3][4]. Cancer itself has been associated with an increased risk of mortality from COVID-19 [5], and it has been recommended to reevaluate interventions to avoid unnecessary exposure [6].…”
Section: Introductionmentioning
confidence: 99%